Efektivitas Teknik Modeling Terhadap Keberhasilan Toilet Training Pada Anak Usia Toddler - Suswojo, Heru; Wiliyanarti, Pipit Festi; Holifah, Nurul; Marini, Gita; Nasrullah, Dede (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The right technique to be given to toddler aage children about toilet training using modeling techniques on the success if toilet training toddlers. Methods: using the literature review method the effectiveness of modeling techniques on the success of toilet training in toddlers. Search articles through the internet with databases: Goggle Scholar, Neliti and ResearchGate. Keywoard: modeling techniques, toilet training, toddler. Inclusion criteria: the purpose of knowing the effectiveness of modeling techniques on the success of toilet training in toddlers, full text, indonesia and english (2015-2020). Retrieved 10 article. Results: : the use of modeling techniques with live models and model for the success of toilet training for toddler by modeling on mother, media conseling with audio-visual, picture modules and demos can improve skills and independence in toilet training. Conclusion: the use of effective modeling techniques using the types of models with video media. The use of video is proven to be effective on the success of toilet training in toddler age children.